Innovations in the Assessment of Skeletal Muscle Health: A Glimpse into the Future - Beausejour, Jonathan P.; Knowles, Kevan S.; Wilson, Abigail T; Mangum, L. Colby; Hill, Ethan C.; Hanney, William J.; Wells, Adam J.; Fukuda, David H.; Stout, JeffreyR.; Stock, Matt S. (International Journal of Sports Medicine, 2024)
Skeletal muscle is the largest organ system in the human body and plays critical roles in athletic performance, mobility, and disease pathogenesis. Despite growing recognition of its importance by major health organizations, significant knowledge gaps remain regarding skeletal muscle health and its crosstalk with nearly every physiological system. Relevant public health challenges like pain, injury, obesity, and sarcopenia underscore the need to accurately assess skeletal muscle health and function. Feasible, non-invasive techniques that reliably evaluate metrics including muscle pain, dynamic structure, contractility, circulatory function, body composition, and emerging biomarkers are imperative to unraveling the complexities of skeletal muscle. Our concise review highlights innovative or overlooked approaches for comprehensively assessing skeletal muscle in vivo. We summarize recent advances in leveraging dynamic ultrasound imaging, muscle echogenicity, tensiomyography, blood flow restriction protocols, molecular techniques, body composition, and pain assessments to gain novel insight into muscle physiology from cellular to whole-body perspectives. Continued development of precise, non-invasive tools to investigate skeletal muscle are critical in informing impactful discoveries in exercise and rehabilitation science.
Keywords: pain; injury; rehabilitation; athlete performance; blood flow restriction; muscle quality